'Academia Inc.': The Perspective of University Presidents - Mount, Joan; Belanger, Charles (Canadian Journal of Higher Education, 2001)
With the erosion of public funding, Canadian universities have increasingly diversified their funding base. An upsurge of entrepreneurial initiatives has displayed significant earmarks of privatization which have alarmed some faculty and student stakeholders, drawing reactions particularly from among those from the arts domains. They accuse senior university administrative officers of distorting academic values. This study is an attempt to capture and understand the views of presidents of Canadian universities (N = 89) through a 60-item questionnaire focused in broad terms on academic values, funding, institutional directions, and the impact of the corporate sector.